2024
DOI: 10.3390/nu16030436
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Criteria and Measurement Techniques of Sarcopenia: A Critical Evaluation of the Up-to-Date Evidence

Gavriela Voulgaridou,
Stefanos Tyrovolas,
Paraskevi Detopoulou
et al.

Abstract: Sarcopenia, a geriatric syndrome characterized by progressive skeletal muscle mass and function decline, poses a significant health risk among the elderly, contributing to frailty, falls, hospitalization, loss of independence and mortality. The prevalence of sarcopenia varies significantly based on various factors, such as living status, demographics, measurement techniques and diagnostic criteria. Although the overall prevalence is reported at 10% in individuals aged 60 and above, disparities exist across set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 116 publications
0
1
0
Order By: Relevance
“…For instance, Liu et al [ 42 ] found that, in Chinese adults ≥ 50 years, the prevalence of sarcopenia according to different operational definitions were 11.8% (EWGSOP2), 18.1% (FNIH), 22.8% (AWGS 2019), 24.1% (IWGS), and 57.1% (EWGSOP1). However, there are other factors such as age group, gender, geographical areas, ethnicities, or locations that may affect the prevalence of sarcopenia [ 43 , 44 ]. A meta-analysis published by Petermann-Rocha et al [ 45 ] described that the prevalence of sarcopenia varied from 10% to 27% in adults aged 60 years and over, where the highest prevalence was found in Oceania (EWGSOP1) and the lowest in Europe (EWGSOP2).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Liu et al [ 42 ] found that, in Chinese adults ≥ 50 years, the prevalence of sarcopenia according to different operational definitions were 11.8% (EWGSOP2), 18.1% (FNIH), 22.8% (AWGS 2019), 24.1% (IWGS), and 57.1% (EWGSOP1). However, there are other factors such as age group, gender, geographical areas, ethnicities, or locations that may affect the prevalence of sarcopenia [ 43 , 44 ]. A meta-analysis published by Petermann-Rocha et al [ 45 ] described that the prevalence of sarcopenia varied from 10% to 27% in adults aged 60 years and over, where the highest prevalence was found in Oceania (EWGSOP1) and the lowest in Europe (EWGSOP2).…”
Section: Discussionmentioning
confidence: 99%
“… 32 As the aetiology is multifactorial and the resulting outcomes are often severe and include increased mortality, disability and reduced quality of life, sarcopenia can be defined as a geriatric syndrome, which warrants specific interventions to prevent its associated negative outcomes. 33 , 34 In this study, we have tested the association between different physical function tests, which to some degree reflect the geriatric syndrome, and fracture outcomes to identify a risk that might be reversible.…”
Section: Discussionmentioning
confidence: 99%